Chloroplast expression of His-tagged GUS-fusions: a general strategy to overproduce and purify foreign proteins using transplastomic plants as bioreactors - Leelavathi, S.; Reddy, V.S.
High level expression and efficient recovery of recombinant protein are two main critical factors that determine the use of transgenic plants as natural bioreactors to produce foreign proteins for industrial applications. We demonstrate here the potential of a new strategy involving chloroplast transformation, GUS-fusions and affinitytag based chromatography to overexpress and purify a human therapeutic protein, interferon gamma (IFN-g)in tobacco plants. Our results show that IFN-g accumulation reaches up to 6
Keywords: AFFINITY CHROMATOGRAPHY; CHLOROPLAST EXPRESSION; GUS-FUSION; HIS-TAG; INTERFERON GAMMA